Optical humidity sensor based on G/GO nanosheets - Nafiseh Tobeiha; Nafiseh Memarian; Fatemeh Ostovari (Scientific Reports)
Abstract Relative humidity (RH) is crucial due to its significant role in various aspects of our lives. Controlling and measuring relative humidity is essential for applications such as detecting human body humidity and heating, air conditioning, and HVAC domestic systems. In the present research, the sonochemical exfoliation method prepares graphene/graphene oxide (G/GO) nanosheets. The physical characteristics of these nanosheets were investigated using essential analysis. Then the optical-humidity sensor was made based on G/GO. This study explored the effect of different humidity percentages based on G/GO nanosheets at room temperature and the impact of various laser wavelengths on the humidity-sensing capabilities of G/GO nanosheets. The sensor’s response and recovery times were examined under different humidity levels and when exposed to 450 nm and 808 nm lasers. The findings demonstrate that the optical-humidity sensor fabricated from G/GO nanosheets, when illuminated by a 450 nm laser across various humidity conditions, outperforms sensors exposed to other laser wavelengths. This highlights the superior efficacy of the 450 nm laser in enhancing the sensor’s performance.